Successful management of gastropulmonary fistula due to invasive fungal infection after chemotherapy and autologous stem cell transplantation: a case report - Janilionis, Ričardas; Lukoševičiūtė, Lina; Beiša, Virgilijus; Jotautas, Valdemaras; Petrauskaitė, Roberta; Pečeliūnas, Valdas; Jucaitienė, Renata (Acta medica Lituanica, 2016)
Background. Invasive fungal infections (IFI) contribute significantly to mortality and morbidity in patients receiving myelosuppressive chemotherapy for hematologic malignancies. Acquired gastropulmonary fistula is a rare complication of IFI. Material and methods. We present a case history of a patient with malignant myeloma. She was treated with autologous stem cell transplantation and chemotherapy for three years. She had been treated with antifungal agents as well. Following a specific treatment, she developed an invasive fungal infection (IFI) of the left lung which had been complicated with left gastropulmonary fistula. The patient’s general condition was deteriorating, so it was decided to perform a surgical intervention. At the first procedure, open-window thoracostomy was created in order to facilitate treatment by daily packing of the cavity. Four weeks after the  thoracostomy, a  thoracomyoplasty was performed to repair a gastropleural fistula. During the laparotomy, the gastric fundus was freed from adjacent tissues and repaired. Intrathoracic transposition of the latissimus dorsi and anterior serratus muscle flaps was performed simultaneously to create a new diaphragm. The open-window thoracostomy was left open due to some small bronchial fistulas. The thoracostomy opening healed spontaneously during the following six months. Conclusion. We report what is, to the best of our knowledge, the first case of an invasive fungal infection (Geotrichum capitatum) successfully treated with intravenous amphotericin B, voriconazole, and surgery on infected soft tissues (organs) for a patient with multiple myeloma in prolonged neutropenia. The efficacy and safety of the surgery for infected soft tissues requires further evaluation.
Keywords: invasive fungal infection after immunosuppresive chemotherapy; pulmonary resection; acquired gastropulmonary fistula